A formação de licenciandos e licenciandas em Química no contexto da Internet das Coisas: possibilidades e desafios emancipatórios - Gomes, Caroindes Julia Corrêa (Universidade Federal de São Carlos, 2022)
This research dialogues with the possibilities and challenges of teacher training in Chemistry for the construction of fairer and sustainable realities, mainly, based on the comprehension of the current time in its coming into being. For this purpose, it was carried out a case study analyzing the formative experiences provided by the disciplines Introduction to Green Chemistry and Information and Communication Technologies applied to Chemistry Education – offered in the Chemistry Teacher Training course at Federal University of São Carlos as a result of curricular reformulations. Using Textual Discourse Analysis, the students' self-evaluations and the didactic sequences elaborated by them were examined, which brought up categories that represented the senses attributed to educative praxes and in which way they were (re) constructed by undergraduates. The capture of the new emerging elements resulted in the construction of four metatexts, in which it was added, when pertinent, phrases collected either from our analysis material or our class observation registers, aiming to approach the completeness of what was manifested. Based on the interfaces between STSE scientific education and Critical Theory, the disciplines fostered systemic and interdisciplinary thought, the examination and questioning of socioscientific controversies, as well as other experiences and perspectives on the teachers’ professionalization. The elaboration of the undergraduates’ proposals aimed at the active participation of the Elementary School students founded on cooperative dynamics and the representation of different voices. However, some developments evinced duality between the apprehended theory and the materialized praxis in the school space, but the process was fundamental for the undergraduates to perceive themselves as teachers, provoke, reconstruct and move on. The undergraduates' commitment and dedication to the activities were observable – except for the texts reading low engagement – which might be a reflection of the relations in digital culture. The results have also revealed the students’ need to “digitize” their experiences and actions, using digital tools in the activities without theoretical and methodological worries. That fetishization was discussed and questioned in different formative moments, including works elaborated by the undergraduates – underpinned by definite spaces and time – and, as a result, it extracted tools from the emancipatory potentialities. These research perspectives foster the comprehension of teacher training in Chemistry in the light of STSE critical scientific education. The horizons emerging from this research point to the need of looking at professionalization based on the distance between theory and praxis, with local problems and possible solutions.
The education of Chemistry Teacher Training in the context of the Internet of Things: emancipatory possibilities and challenges
Keywords: Formação docente; Educação em Química; Internet das Coisas; CTSA; Teoria Crítica; Teacher training; Chemistry Education; Internet of Things; STSE; Critical Theory; CIENCIAS HUMANAS::EDUCACAO